Makna AI-Qalb dan Bentuk Pengungkapannya dalam AI-Quran - Agustiar, Agustiar (Jurnal Ushuluddin, 2013)
Man equipped by God Almighty with a variety of gifts that enable them to bear the burden of the task. The gifts are a power of the body, vitality and Al-Qalb. Islam has made clear the necessity of the proper fungtioning of al-qalb for thinking in order to develop knowledge, which in turn will help people in the task of his chaliphate on earth with good and true under the guidance of al-quran and al-hadits. One way to improve the taste of qalb which islam is required by dzikir and when someone will find peace of mind and feel close to god. With feeling close to god oneâs soul will be controlled. Conversely if a person is not functioning his qalb for dzikir, he will suffer from drought soul. In the al-quran, al-qalb has a variety of meanings, ccording to the contex of the paragraph that contains the word. In addition, to demonstrate the meaning of al-qalb not always expressed with the word al-qalb, but but often also expressed by using the word al-fuad, al-lub, al-nafs and al-sadr